Self-adhesive coiled material for concrete pavement repair and preparation method thereof

By using modified polymer substrates and self-adhesive glue in pavement repair materials, combined with linoleic acid-POSS composite, the problems of long traffic interruption time and easy material cracking in existing pavement repair methods are solved, and high efficiency is achieved. Durable road surface repair effect.

CN118909556BActive Publication Date: 2024-12-24HUNAN SHENGYE TUGONG MATERIALS MFG CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411421872.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-24
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing road surface repair methods require the cooperation of large equipment and personnel, resulting in long traffic interruption time and repair materials are prone to cracking under vehicle loads, making it difficult to maintain good protective effects for a long time.

Method used

Using self-adhesive coils, by coating self-adhesive glue on polymer substrates, combining modified kaolin and end-hydroxyl liquid nitrile rubber, the toughness and impact resistance of the material are enhanced, and oily oil is added to the self-adhesive glue. Acid-POSS complex improves heat resistance and waterproofing.

Benefits of technology

It realizes lightweight, high compression and waterproof road surface repair materials, reduces traffic interruption time, improves the durability and service life of the material, and can effectively resist vehicle loads and moisture intrusion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses a self-adhesive coiled material for repairing a concrete pavement and a preparation method thereof, and belongs to the technical field of pavement repair. The self-adhesive coiled material prepared by the invention has the characteristics of being lightweight, basically does not increase the deadweight of the original pavement, has good compressive strength, toughness, tensile strength and bonding strength, can well withstand vehicle loads without being damaged, has strong waterproof and water-resistant capabilities, and can effectively protect the pavement from water damage; the pavement construction and repair procedures are simple, the road closure time is short, the road closure range is small, and the impact on vehicle traffic is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road surface repair, and in particular to a self-adhesive coiled material for repairing a concrete road surface and a preparation method thereof. Background Art

[0002] Pavement repair is an important part of urban infrastructure management. The inherent defects in the design and construction of cement concrete pavements, as well as the repeated effects of automobile and temperature loads during service, will lead to the aging of binders, aggregate shedding, insufficient skid resistance and other defects on the surface layer of cement pavements. In particular, fatigue and reflective cracks will lead to a decrease in structural strength and increased water seepage, which will accelerate the expansion of minor defects to moderate and severe defects, seriously affecting driving safety and the service life of the pavement. In order to prevent the further expansion of cement pavement cracks caused by stress concentration, and then cause concrete slab breakage and pavement slurry and mud pumping, and to ensure the integrity of the pavement and driving safety, timely and effective caulking and repairing measures should be taken for cement pavement cracks.

[0003] At present, the general method of repairing cracks is to dig grooves in the damaged road surface, spread hot asphalt, or use large machinery to seal the surface. On the one hand, these two methods require long-term traffic interruption, and on the other hand, they also require large equipment vehicles such as asphalt spreaders, rollers, trenchers, and multiple road maintenance personnel to work together, which is labor-intensive and time-consuming. Especially in areas with heavy traffic, road interruption construction will bring great instability to the travel of people and vehicles.

[0004] Chinese patent document CN106087642A discloses a method and material for repairing cracks and peeling of pavement. The material used in this application is a modified asphalt sheet, which lacks a flexible buffer layer and is directly subjected to the impact of vehicle loads. Under repeated rolling of vehicles, the asphalt layer is prone to cracking, making it difficult to maintain a good protective effect for a long time. Summary of the invention

[0005] The main purpose of the present invention is to propose a self-adhesive roll material for repairing concrete pavement. The roll material is a composite material obtained by coating a self-adhesive adhesive on one side of a geotextile. The composite structure enhances the toughness of the overall structure, improves the resistance to external loads, can better adapt to slight deformations of the road surface, and reduces damage to the road surface during vehicle operation.

[0006] To achieve the above-mentioned purpose, the present invention proposes a self-adhesive roll material for repairing concrete pavement, comprising a polymer substrate and a self-adhesive coated on one side of the polymer substrate, wherein the polymer substrate is composed of the following raw materials by weight: 10-20 parts of polypropylene resin, 3-5 parts of modifier, and 0.1-0.3 parts of antioxidant.

[0007] Preferably, the preparation method of the modifier is as follows:

[0008] (1) soaking kaolin in a dilute acid aqueous solution, heating and stirring, cooling, standing, filtering, collecting solids, washing, drying, grinding and sieving to obtain pretreated kaolin;

[0009] (2) adding the pretreated kaolin to anhydrous ethanol, adding epichlorohydrin, tetraethylenepentamine, 4-amino-3-hydroxybenzoic acid, and NaOH aqueous solution, heating to react, cooling, filtering to collect solids, washing and drying the solids to obtain modified kaolin;

[0010] (3) Dispersing the modified kaolin in anhydrous ethanol, adding hydroxyl-terminated liquid nitrile rubber and NaOH aqueous solution, heating for reaction, cooling and filtering after the reaction is completed, washing and drying to obtain a modifier.

[0011] Further preferably, in the step (1), the mass ratio of kaolin to the dilute acid aqueous solution is 1:10-20; the concentration of the dilute acid aqueous solution is 10-20wt%; and the heating temperature is 40-60°C.

[0012] Further preferably, in the step (2), the mass ratio of pretreated kaolin, epichlorohydrin, tetraethylenepentamine and 4-amino-3-hydroxybenzoic acid is 20-30:10-15:5-8:6-10; and the heating temperature is 60-80°C.

[0013] Further preferably, in the step (3), the mass ratio of modified kaolin to hydroxyl-terminated liquid nitrile rubber is 10-15:8-10; and the heating temperature is 60-80°C.

[0014] Preferably, the antioxidant is one of phosphite, butylated hydroxyanisole and butylated hydroxytoluene.

[0015] The polymer substrate of the present invention is a geotextile formed by spinning, pulling, laying, needle punching and hot rolling after melting polypropylene resin. The mechanical properties of the polymer substrate can be significantly improved by adding a modifier. First, kaolin is treated with acid, which is beneficial to the activation of its surface functional groups. Tetraethylenepentamine and 4-amino-3-hydroxybenzoic acid with more active functional groups are introduced on the surface through the cross-linking effect of epichlorohydrin. In the process of mixed melt spinning, they are cross-linked with each other, which is beneficial to the improvement of the tear resistance of the polymer substrate. Hydroxyl-terminated liquid nitrile rubber is grafted on the surface, so that the toughness and impact resistance of the polymer substrate are significantly improved, so that the risk of fracture of the polymer substrate when being crushed by a vehicle can be significantly reduced, thereby improving the durability of the polymer substrate.

[0016] Preferably, the preparation method of the self-adhesive is as follows: by mass, 20-40 parts of epoxy resin, 15-20 parts of white oil, 10-20 parts of nano-calcium carbonate, 0.1-3 parts of diisononyl phthalate, 1-5 parts of hexahydrophthalic anhydride, and 3-5 parts of linoleic acid-POSS complex are stirred and mixed uniformly to obtain the self-adhesive.

[0017] Preferably, the preparation method of the linoleic acid-POSS complex is as follows:

[0018] After the aminophenyl POSS and toluene are mixed evenly, linoleic acid, 1-ethyl-(3-dimethylaminopropyl)carbodiimide and citrate buffer are added, and then stirred at 40-60° C. for 4-6 hours, and the solvent is evaporated under reduced pressure to obtain a linoleic acid-POSS complex.

[0019] Preferably, the mass ratio of the aminophenyl POSS, linoleic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 10-15:6-8:5-7; and the heating temperature is 40-60°C.

[0020] Aminephenyl POSS is a new type of nanostructured hybrid material. Aminephenyl POSS has the advantages of organic and inorganic nanomaterials, and its thermal stability is outstanding. It can enhance the heat resistance, mechanical properties, and flame retardant properties of self-adhesives and improve the processing properties of materials. Linoleic acid with a long fatty chain is grafted on its surface. Linoleic acid has a long hydrophobic alkyl long chain structure. Introducing it into the self-adhesive can effectively reduce the hydrophilicity of the self-adhesive, effectively prevent moisture from penetrating into the pavement base, and reduce pavement damage caused by moisture intrusion. The multiple active amino groups on the aminephenyl POSS molecule can form strong hydrogen bonds with the base pavement, enhancing the bonding ability with the pavement. By adding linoleic acid-POSS complex to the self-adhesive, the heat resistance and toughness of the self-adhesive are significantly improved.

[0021] Preferably, the method for preparing the self-adhesive coiled material for repairing concrete pavement comprises the following steps: mixing and melting a polypropylene resin, a modifier and an antioxidant to obtain a melt, and sequentially spinning, pulling, laying, needling and hot rolling the melt to obtain a polymer substrate; uniformly coating one side of the polymer substrate with a self-adhesive adhesive, attaching an isolation film to the side of the self-adhesive adhesive away from the substrate, allowing to stand at room temperature, and finally rolling the self-adhesive coiled material for repairing concrete pavement to obtain the self-adhesive coiled material for repairing concrete pavement.

[0022] Preferably, the melting temperature is 230-250°C, and the melt flow rate is 19-25g / 10min.

[0023] Preferably, the polymer substrate has a length of 200-300 m and a width of 3.6-3.8 m.

[0024] Preferably, the coating amount of the self-adhesive is 100-200 g / m 2 .

[0025] Preferably, the isolation film is one of a polypropylene film and a PET film.

[0026] Preferably, the thickness of the self-adhesive coil is 0.6-1.5 mm.

[0027] The invention also discloses a method for using the self-adhesive coiled material for repairing concrete pavement: removing the isolation film on the self-adhesive coiled material for repairing concrete pavement, and directly applying it to the pavement to be repaired or correctively maintained.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The self-adhesive coiled material prepared by the present invention is lightweight, does not substantially increase the deadweight of the original road surface, has good compressive strength, toughness, tensile strength and bonding strength, can well withstand vehicle loads without damage, has strong waterproof capability, and can effectively protect the road surface from water damage; the road surface construction and repair process is simple, the road closure time is short, the road closure range is small, and the impact on vehicle traffic is reduced;

[0030] 2. The present invention can significantly improve the tear resistance of the polymer substrate by adding a modifier to the polymer substrate, thereby significantly reducing the risk of fracture of the polymer substrate when it is crushed by a vehicle, and improving the durability of the polymer substrate;

[0031] 3. The present invention can effectively reduce the hydrophilicity of the self-adhesive by adding the linoleic acid-POSS complex to the self-adhesive, effectively prevent water from penetrating into the road base, and reduce road damage caused by water intrusion; the heat resistance and toughness of the self-adhesive are significantly improved, thereby increasing the service life of the self-adhesive. DETAILED DESCRIPTION

[0032] To avoid redundancy, the items used in the following examples are all commercially available products unless otherwise specified, and the methods used are all conventional methods unless otherwise specified.

[0033] The sources of some raw materials used in the present invention are as follows:

[0034] Polypropylene resin, brand PP FD905U, was purchased from Dongguan Yuming Plastic Technology Co., Ltd.

[0035] Kaolin, 325 mesh, was purchased from Lingshou County Jiaao Mineral Products Co., Ltd.

[0036] Epoxy resin, with an epoxy value of 0.57 equivalent / 100 g, was purchased from Hunan Jingyuan New Material Technology Co., Ltd.

[0037] Amine phenyl POSS was purchased from Angxing New Carbon Materials Changzhou Co., Ltd.

[0038] Hydroxyl-terminated liquid nitrile rubber, model SH-820, was purchased from Jining Tangyi Chemical Co., Ltd.

[0039] Nano calcium carbonate, 325 mesh, was purchased from Zhenhe Mineral Products Processing Plant in Lingshou County. Example 1

[0040] A self-adhesive coiled material for repairing a concrete pavement, and a preparation method thereof, comprising the following steps: 150g of polypropylene resin, 42.8g of a modifier, and 2g of butylated hydroxyanisole are mixed and then melted at 240°C to obtain a melt, wherein the melt flow rate is 22g / 10min, and the melt is sequentially subjected to spinning, traction, web laying, needling, and hot rolling by a calendering machine to obtain a polymer substrate; 300g of epoxy resin, 170g of white oil, 168g of nano-calcium carbonate, 15g of diisononyl phthalate, 23g of hexahydrophthalic anhydride, and 40g of a linoleic acid-POSS complex are stirred and mixed to obtain a self-adhesive, and the self-adhesive is evenly coated on one side of the polymer substrate, wherein the coating amount of the self-adhesive is 150g / m 2 , and attach a PET film to the side of the self-adhesive away from the polymer substrate, let it stand at room temperature for 30 minutes, and finally roll it to obtain the self-adhesive roll material for concrete pavement repair.

[0041] The preparation method of the modifier is as follows:

[0042] (1) 30 g of kaolin was immersed in 450 mL of 15 wt% dilute sulfuric acid aqueous solution, heated and stirred at 50 °C for 2 h, cooled, allowed to stand, filtered, and the solid was collected, washed, dried, ground and sieved to obtain pretreated kaolin;

[0043] (2) Add 25 g of pretreated kaolin to 200 mL of anhydrous ethanol, add 12.8 g of epichlorohydrin, 6.5 g of tetraethylenepentamine, 8.3 g of 4-amino-3-hydroxybenzoic acid, and 10 mL of 1 mol / L NaOH aqueous solution, react at 70 °C for 4 h, cool, filter and collect the solid, wash and dry the solid to obtain modified kaolin;

[0044] (3) Disperse 12.6 g of modified kaolin in 200 mL of anhydrous ethanol, add 9.2 g of hydroxyl-terminated liquid nitrile rubber and 5 mL of 1 mol / L NaOH aqueous solution, heat at 70 °C for 2 h, cool and filter after the reaction is completed, wash and dry to obtain the modifier.

[0045] The preparation method of the linoleic acid-POSS complex is as follows:

[0046] 12.4 g of aminophenyl POSS and 200 mL of toluene were mixed evenly, and then 7.3 g of linoleic acid, 6 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 45 mL of citrate buffer were added, followed by stirring at 50° C. for 6 h, and the solvent was evaporated under reduced pressure to obtain a linoleic acid-POSS complex. Example 2

[0047] A self-adhesive coiled material for repairing concrete pavement, and a preparation method thereof, comprising the following steps:

[0048] 100g of polypropylene resin, 30.5g of modifier and 1.1g of butylated hydroxyanisole were mixed and melted at 230°C to obtain a melt, wherein the melt flow rate was 19g / 10min. The melt was sequentially subjected to spinning, traction, web laying, needle punching and hot rolling by a calendering machine to obtain a polymer substrate. 200g of epoxy resin, 150g of white oil, 100g of nano-calcium carbonate, 1g of diisononyl phthalate, 10g of hexahydrophthalic anhydride and 30g of linoleic acid-POSS complex were stirred and mixed to obtain the self-adhesive, and the self-adhesive was evenly coated on one side of the polymer substrate, and the coating amount of the self-adhesive was 100g / m 2 , and attach a PET film to the side of the self-adhesive away from the polymer substrate, let it stand at room temperature for 30 minutes, and finally roll it to obtain the self-adhesive roll material for concrete pavement repair.

[0049] The preparation method of the modifier is as follows:

[0050] (1) 30 g of kaolin was immersed in 300 mL of 10 wt% dilute sulfuric acid aqueous solution, heated and stirred at 40 °C for 2 h, cooled, allowed to stand, filtered, and the solid was collected, washed, dried, ground and sieved to obtain pretreated kaolin;

[0051] (2) Add 20 g of pretreated kaolin to anhydrous ethanol, add 10.5 g of epichlorohydrin, 5.2 g of tetraethylenepentamine, 6 g of 4-amino-3-hydroxybenzoic acid, and 10 mL of 1 mol / L NaOH aqueous solution, heat at 60 ° C for 4 h, cool, filter and collect solids, wash and dry the solids to obtain modified kaolin;

[0052] (3) Disperse 10 g of modified kaolin in 200 mL of anhydrous ethanol, add 8 g of hydroxyl-terminated liquid nitrile rubber and 5 mL of 1 mol / L NaOH aqueous solution, heat at 60 °C for 2 h, cool and filter after the reaction is completed, wash and dry to obtain the modifier.

[0053] The preparation method of the linoleic acid-POSS complex is as follows:

[0054] After 10 g of aminophenyl POSS and 200 mL of toluene were mixed evenly, 6.5 g of linoleic acid, 5.3 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 45 mL of citrate buffer were added, and then stirred at 40° C. for 6 h. The solvent was evaporated under reduced pressure to obtain a linoleic acid-POSS complex. Example 3

[0055] A self-adhesive coiled material for repairing a concrete pavement, and a preparation method thereof, comprising the following steps: 200g of polypropylene resin, 50g of a modifier, and 3g of butylated hydroxyanisole are mixed and then melted at 250°C to obtain a melt, wherein the melt flow rate is 25g / 10min; the melt is sequentially subjected to spinning, traction, web laying, needling, and hot rolling by a calendering machine to obtain the polymer substrate; 400g of epoxy resin, 200g of white oil, 200g of nano-calcium carbonate, 30g of diisononyl phthalate, 50g of hexahydrophthalic anhydride, and 50g of a linoleic acid-POSS complex are stirred and mixed to obtain the self-adhesive; the self-adhesive is evenly coated on one side of the polymer substrate, and the coating amount of the self-adhesive is 200g / m 2 , and attach a PET film to the side of the self-adhesive away from the polymer substrate, let it stand at room temperature for 30 minutes, and finally roll it to obtain the self-adhesive roll material for concrete pavement repair.

[0056] The preparation method of the modifier is as follows:

[0057] (1) 30 g of kaolin was immersed in 600 mL of 20 wt% dilute sulfuric acid aqueous solution, heated and stirred at 60 °C for 2 h, cooled, allowed to stand, filtered, solids were collected, washed, dried, ground and sieved to obtain pretreated kaolin;

[0058] (2) Add 29.5 g of pretreated kaolin to 200 mL of anhydrous ethanol, add 14.8 g of epichlorohydrin, 8 g of tetraethylenepentamine, 10 g of 4-amino-3-hydroxybenzoic acid, and 10 mL of 1 mol / L NaOH aqueous solution, react at 80 °C for 4 h, cool, filter and collect the solid, wash and dry the solid to obtain modified kaolin;

[0059] (3) Disperse 15 g of modified kaolin in 200 mL of anhydrous ethanol, add 10 g of hydroxyl-terminated liquid nitrile rubber and 5 mL of 1 mol / L NaOH aqueous solution, heat at 80 °C for 2 h, cool and filter after the reaction is completed, wash and dry to obtain the modifier.

[0060] The preparation method of the linoleic acid-POSS complex is as follows:

[0061] After 15 g of aminophenyl POSS and 200 mL of toluene were mixed evenly, 8 g of linoleic acid, 7 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 45 mL of citrate buffer were added, and then stirred at 60° C. for 4 h. The solvent was evaporated under reduced pressure to obtain a linoleic acid-POSS complex.

[0062] Comparative Example 1

[0063] A self-adhesive coiled material for repairing concrete pavement, the preparation method of which is similar to that of Example 1, except that no modifier is added in the preparation method of a polymer substrate, and specifically comprises the following steps: 150g of polypropylene resin and 2g of butylated hydroxyanisole are mixed and then melted at 240°C to obtain a melt, wherein the melt flow rate is 22g / 10min, and the melt is sequentially subjected to spinning, traction, web laying, needling, and hot rolling by a calendering machine to obtain a polymer substrate; 300g of epoxy resin, 170g of white oil, 168g of nano-calcium carbonate, 15g of diisononyl phthalate, 23g of hexahydrophthalic anhydride, and 40g of linoleic acid-POSS composite are stirred and mixed to obtain the self-adhesive, and the self-adhesive is evenly coated on one side of the polymer substrate, and the coating amount of the self-adhesive is 150g / m 2 , and attach a PET film to the side of the self-adhesive away from the polymer substrate, let it stand at room temperature for 30 minutes, and finally roll it to obtain the self-adhesive roll material for concrete pavement repair.

[0064] The preparation method of the linoleic acid-POSS complex is as follows:

[0065] 12.4 g of aminophenyl POSS and 200 mL of toluene were mixed evenly, and then 7.3 g of linoleic acid, 6 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 45 mL of citrate buffer were added, followed by stirring at 50° C. for 6 h, and the solvent was evaporated under reduced pressure to obtain a linoleic acid-POSS complex.

[0066] Comparative Example 2

[0067] A self-adhesive coiled material for repairing concrete pavement, a preparation method thereof, similar to that of Example 1, except that no linoleic acid-POSS complex is added in the preparation method of the self-adhesive, and specifically comprises the following steps: 150g of polypropylene resin, 42.8g of a modifier, and 2g of butylated hydroxyanisole are mixed and then melted at 240°C to obtain a melt, wherein the melt flow rate is 22g / 10min, and the melt is sequentially subjected to spinning, traction, web laying, needling, and hot rolling by an ironing machine to obtain a polymer substrate; 300g of epoxy resin, 170g of white oil, 168g of nano-calcium carbonate, 15g of diisononyl phthalate, and 23g of hexahydrophthalic anhydride are stirred and mixed to obtain the self-adhesive, and the self-adhesive is evenly coated on one side of the polymer substrate, and the coating amount of the self-adhesive is 150g / m 2, and attach a PET film to the side of the self-adhesive away from the polymer substrate, let it stand at room temperature for 30 minutes, and finally roll it to obtain the self-adhesive roll material for concrete pavement repair.

[0068] The preparation method of the modifier is as follows:

[0069] (1) 30 g of kaolin was immersed in 450 mL of 15 wt% dilute sulfuric acid aqueous solution, heated and stirred at 50 °C for 2 h, cooled, allowed to stand, filtered, and the solid was collected, washed, dried, ground and sieved to obtain pretreated kaolin;

[0070] (2) Add 25 g of pretreated kaolin to 200 mL of anhydrous ethanol, add 12.8 g of epichlorohydrin, 6.5 g of tetraethylenepentamine, 8.3 g of 4-amino-3-hydroxybenzoic acid, and 10 mL of 1 mol / L NaOH aqueous solution, react at 70 °C for 4 h, cool, filter and collect the solid, wash and dry the solid to obtain modified kaolin;

[0071] (3) Disperse 12.6 g of modified kaolin in 200 mL of anhydrous ethanol, add 9.2 g of hydroxyl-terminated liquid nitrile rubber and 5 mL of 1 mol / L NaOH aqueous solution, heat at 70 °C for 2 h, cool and filter after the reaction is completed, wash and dry to obtain the modifier.

[0072] Comparative Example 3

[0073] A self-adhesive coiled material for repairing concrete pavement, the preparation method of which is similar to that of Example 1, except that the modifier added to the polymer substrate is modified kaolin, and specifically comprises the following steps: 150g of polypropylene resin, 42.8g of modifier, and 2g of butylated hydroxyanisole are mixed and then melted at 240°C to obtain a melt, wherein the melt flow rate is 22g / 10min, and the melt is sequentially subjected to spinning, traction, web laying, needling, and hot rolling by a calendering machine to obtain a polymer substrate; 300g of epoxy resin, 170g of white oil, 168g of nano-calcium carbonate, 15g of diisononyl phthalate, 23g of hexahydrophthalic anhydride, and 40g of linoleic acid-POSS complex are stirred and mixed to obtain the self-adhesive, and the self-adhesive is evenly coated on one side of the polymer substrate, and the coating amount of the self-adhesive is 150g / m 2 , and attach a PET film to the side of the self-adhesive away from the polymer substrate, let it stand at room temperature for 30 minutes, and finally roll it to obtain the self-adhesive roll material for concrete pavement repair.

[0074] The preparation method of the modifier is as follows:

[0075] (1) 30 g of kaolin was immersed in 450 mL of 15 wt% dilute sulfuric acid aqueous solution, heated and stirred at 50 °C for 2 h, cooled, allowed to stand, filtered, and the solid was collected, washed, dried, ground and sieved to obtain pretreated kaolin;

[0076] (2) Add 25 g of pretreated kaolin to 200 mL of anhydrous ethanol, add 12.8 g of epichlorohydrin, 6.5 g of tetraethylenepentamine, 8.3 g of 4-amino-3-hydroxybenzoic acid, and 10 mL of 1 mol / L NaOH aqueous solution, react at 70 °C for 4 h, cool, filter and collect the solid, wash and dry the solid to obtain modified kaolin, which is the modifier.

[0077] The preparation method of the linoleic acid-POSS complex is as follows:

[0078] 12.4 g of aminophenyl POSS and 200 mL of toluene were mixed evenly, and then 7.3 g of linoleic acid, 6 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 45 mL of citrate buffer were added, followed by stirring at 50° C. for 6 h, and the solvent was evaporated under reduced pressure to obtain a linoleic acid-POSS complex.

[0079] Comparative Example 4

[0080] A self-adhesive coiled material for repairing concrete pavement, a preparation method thereof, similar to that of Example 1, except that phenylamine POSS in the self-adhesive is not modified, specifically comprising the following steps: 150g of polypropylene resin, 42.8g of a modifier, and 2g of butylated hydroxyanisole are mixed and then melted at 240°C to obtain a melt, wherein the melt flow rate is 22g / 10min, and the melt is sequentially subjected to spinning, traction, web laying, needling, and hot rolling by a calendering machine to obtain a polymer substrate; 300g of epoxy resin, 170g of white oil, 168g of nano-calcium carbonate, 15g of diisononyl phthalate, 23g of hexahydrophthalic anhydride, and 40g of phenylamine POSS are stirred and mixed to obtain the self-adhesive, and the self-adhesive is evenly coated on one side of the polymer substrate, and the coating amount of the self-adhesive is 150g / m 2 , and attach a PET film to the side of the self-adhesive away from the polymer substrate, let it stand at room temperature for 30 minutes, and finally roll it to obtain the self-adhesive roll material for concrete pavement repair.

[0081] The preparation method of the modifier is as follows:

[0082] (1) 30 g of kaolin was immersed in 450 mL of 15 wt% dilute sulfuric acid aqueous solution, heated and stirred at 50 °C for 2 h, cooled, allowed to stand, filtered, and the solid was collected, washed, dried, ground and sieved to obtain pretreated kaolin;

[0083] (2) Add 25 g of pretreated kaolin to 200 mL of anhydrous ethanol, add 12.8 g of epichlorohydrin, 6.5 g of tetraethylenepentamine, 8.3 g of 4-amino-3-hydroxybenzoic acid, and 10 mL of 1 mol / L NaOH aqueous solution, react at 70 °C for 4 h, cool, filter and collect the solid, wash and dry the solid to obtain modified kaolin;

[0084] (3) Disperse 12.6 g of modified kaolin in 200 mL of anhydrous ethanol, add 9.2 g of hydroxyl-terminated liquid nitrile rubber and 5 mL of 1 mol / L NaOH aqueous solution, heat at 70 °C for 2 h, cool and filter after the reaction is completed, wash and dry to obtain the modifier.

[0085] Test Case

[0086] Tear resistance test of polymer substrate: The test method refers to GB / T3917.2-2009 "Tear properties of textile fabrics Part 2: Determination of tear strength of trouser-shaped test specimens (single seam)", and the tear resistance of the polymer substrates prepared by Examples 1-3 of the present invention, Comparative Example 1, and Comparative Example 3 is tested. The test results are shown in Table 1:

[0087]

[0088] Thermal aging performance test, peeling strength test with concrete: The test objects are the self-adhesives prepared in Examples 1-3, Comparative Example 2, and Comparative Example 4, all of which are tested with reference to GB / T23457-2017 "Pre-laid waterproofing membrane", and the test results are shown in Table 1:

[0089] It can be seen from the experimental results in Table 1 that the self-adhesive roll material for concrete pavement repair prepared by the present invention has good tear resistance, adhesion and heat aging resistance properties.

[0090] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A self-adhesive coiled material for repairing concrete pavement, comprising a polymer substrate and a self-adhesive adhesive coated on one side of the polymer substrate, wherein the polymer substrate is composed of the following raw materials in parts by weight: 10-20 parts of polypropylene resin, 3-5 parts of modifier, 0.1-0.3 parts of antioxidant; The preparation method of the modifier is as follows: (1) soaking kaolin in a dilute acid aqueous solution, heating and stirring, cooling, standing, filtering, collecting solids, washing, drying, grinding and sieving to obtain pretreated kaolin; (2) adding the pretreated kaolin to anhydrous ethanol, adding epichlorohydrin, tetraethylenepentamine, 4-amino-3-hydroxybenzoic acid, and NaOH aqueous solution, heating to react, cooling, filtering to collect solids, washing and drying the solids to obtain modified kaolin; (3) dispersing the modified kaolin in anhydrous ethanol, adding hydroxyl-terminated liquid nitrile rubber and NaOH aqueous solution, heating for reaction, cooling and filtering after the reaction is completed, washing and drying to obtain a modifier; In the step (1), the mass ratio of kaolin to dilute acid aqueous solution is 1:10-20; the concentration of the dilute acid aqueous solution is 10-20wt%; and the heating temperature is 40-60°C; In the step (2), the mass ratio of pretreated kaolin, epichlorohydrin, tetraethylenepentamine, and 4-amino-3-hydroxybenzoic acid is 20-30:10-15:5-8:6-10; In the step (3), the mass ratio of modified kaolin and hydroxyl-terminated liquid nitrile rubber is 10-15:8-10; the preparation method of the self-adhesive adhesive is as follows: by mass, 20-40 parts of epoxy resin, 15-20 parts of white oil, 10-20 parts of nano calcium carbonate, 0.1-3 parts of diisononyl phthalate, 1-5 parts of hexahydrophthalic anhydride, and 3-5 parts of linoleic acid-POSS complex are stirred and mixed to obtain the self-adhesive adhesive; The preparation method of the linoleic acid-POSS complex is as follows: After the aminophenyl POSS and toluene are uniformly mixed, linoleic acid, 1-ethyl-(3-dimethylaminopropyl) carbodiimide and citrate buffer are added, and then stirred at 40-60° C. for 4-6 hours, and the solvent is evaporated under reduced pressure to obtain a linoleic acid-POSS complex; The mass ratio of the aminophenyl POSS, linoleic acid and 1-ethyl-(3-dimethylaminopropyl)carbodiimide is 10-15:6-8:5-7.

2. A method for preparing the coiled material according to claim 1, characterized in that: The method comprises the following steps: mixing and melting a polypropylene resin, a modifier and an antioxidant to obtain a melt, and sequentially spinning, pulling, laying a mesh, needling and hot rolling the melt to obtain a polymer substrate; uniformly coating one side of the polymer substrate with a self-adhesive adhesive, attaching an isolation film to the side of the self-adhesive adhesive away from the substrate, allowing the self-adhesive adhesive to stand at room temperature, and finally rolling the self-adhesive coiled material for concrete pavement repair.

3. The preparation method according to claim 2, characterized in that: The isolation film is one of a polypropylene film and a PET film.